Functional and genomic analyses of blocked protein O-mannosylation in baker's yeast - Arroyo, Javier; Hutzler, Johannes; Ragni, Enrico; Piberger, Heidi; Schott, Andrea; Strahl, Sabine (Molecular microbiology, 2011)
O-mannosylation is a crucial protein modification in eukaryotes that is initiated by the essential family of protein O-mannosyltransferases (PMTs). Here we demonstrate that in the model yeast Saccharomyces cerevisiae rhodanine-3-acetic acid derivatives affect members of all PMT subfamilies. Specifically, we used OGT2468 to analyse genome-wide transcriptional changes in response to general inhibition of O-mannosylation in baker's yeast. PMT inhibition results in the activation of the cell wall integrity (CWI) pathway. Coinciding, the mitogen-activated kinase Slt2p is activated in vivo and CWI pathway mutants are hypersensitive towards OGT2468. Further, induction of many target genes of the unfolded protein response (UPR) and ER-associated protein degradation (ERAD) is observed. The interdependence of O-mannosylation and UPR/ERAD is confirmed by genetic interactions between HAC1 and PMTs, and increased degradation of the ERAD substrate Pdr5p* in pmtΔ mutants. Transcriptome analyses further suggested that mating and filamentous growth are repressed upon PMT inhibition. Accordingly, in vivo mating efficiency and invasive growth are considerably decreased upon OGT2468 treatment. Quantitative PCR and ChIP analyses suggest that downregulation of mating genes is dependent on the transcription factor Ste12p. Finally, inhibitor studies identified a role of the Ste12p-dependent vegetative signalling cascade in the adaptive response to inhibition of O-mannosylation.